Carbapenemase-producing Eenterobacterales from hospital environment and their relation to those from patient specimens - Si Hyun Kim; Gyu Ri Kim; Eun-Young Kim; Joseph Jeong; Sunjoo Kim; Jeong Hwan Shin (Elsevier, 2022)
Background: The hospital environment can be an important source for the transmission of pathogens, However, there are rare reports revealing the contamination of carbapenemase-producing enterobacterales (CPE) in the hospital environment. The aim of this study was to investigate the presence of CPE in hospital environments and their relation to clinical strains. Methods: Environmental samples were collected from three tertiary university hospitals between June 2017 and August 2019. The environmental samples were inoculated on CHROMagar™ KPC plates. A multiplex PCR and sequencing were used for six carbapenemase genes. Multi-locus sequence typing (MLST) was performed for CPE of Klebsiella pneumoniae, Escherichia coli, and Enterobacter cloacae complex from the environmental and clinical specimens. Results: 20 carbapenem-resistant Enterobacteriaceae (CRE) strains were detected in the beds of patients, toilet bowl, sink, patient's gown, electromanometer, and keyboard. K. pneumoniae was the most common, followed by Serratia marcescens, E. cloacae complex, E. coli, and Citrobacter freundii. Nineteen CRE were CPE. Eighteen of 19 CPEs produced KPC-2 carbapenemase, and one CPE (E. coli) produced NDM-5. We confirmed that the STs of K. pneumoniae-producing KPC-2 (ST 307 and ST11) and E. coli producing KPC-2 (ST648) from hospital environment were the same as those from patients. Conclusion: We believe that the hospital environment can be an important route for CPE transmission. Therefore, continuous surveillance and management are needed to prevent hospital-acquired infections (HAI) by transmission of CPE.